2010
DOI: 10.1074/jbc.m110.112599
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin-27 Induces a STAT1/3- and NF-κB-dependent Proinflammatory Cytokine Profile in Human Monocytes

Abstract: IL-27 is a heterodimeric cytokine bridging innate and adaptive immunity by playing a role in the activation of naive T cells and in development of Th1 cells. Additionally, recent evidence supports a role for IL-27 in the activation of monocytic cells. Both pro-inflammatory and anti-inflammatory activities have been attributed to IL-27; however, the role played by IL-27 in the activation of human monocytic cells in terms of cytokine production has not been well described. Our results show that IL-27 is a strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 35 publications
5
85
1
Order By: Relevance
“…However, comparisons of indeterm inate results are difficult to make due to the lack of a validated cutoff for an indeterminate IP-10 response (see below). The immunological mechanisms underlying these suggested differences between IFN-g and IP-10 in HIV-infected patients are as yet unknown, but are probably due to a combination of both the higher magnitude of response and the broader induction profile of IP-10 compared with IFN-g [37][38][39][40][41][42][43][44][45][46]. Sutherland and colleagues recently demonstrated that coincident with the loss of total CD4 count, the TB antigen-specific immune response changed from a polyfunctional CD4 response to a monofunctional IFN-g or TNF-a CD8 T-cell response [74].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, comparisons of indeterm inate results are difficult to make due to the lack of a validated cutoff for an indeterminate IP-10 response (see below). The immunological mechanisms underlying these suggested differences between IFN-g and IP-10 in HIV-infected patients are as yet unknown, but are probably due to a combination of both the higher magnitude of response and the broader induction profile of IP-10 compared with IFN-g [37][38][39][40][41][42][43][44][45][46]. Sutherland and colleagues recently demonstrated that coincident with the loss of total CD4 count, the TB antigen-specific immune response changed from a polyfunctional CD4 response to a monofunctional IFN-g or TNF-a CD8 T-cell response [74].…”
Section: Reviewmentioning
confidence: 99%
“…IP-10 secretion appears to be driven by multiple signals, mainly T-cell-derived IFN-g, but also IL-2, IFN-a, IFN-b, IL-27, IL-17, IL-23, and autocrine APC-derived TNF-a and IL-1b. TNF-a is a weak IP-10 inducer per se, but a potent synergistic inducer when acting with the interferons [37][38][39][40][41][42][43][44][45][46]. Because of the many different pathways that can lead to IP-10 secretion, IP-10 can be considered a downstream marker to typical readout markers in CMI assays, such as IL-2 and IFN-g [47,48].…”
Section: The Immunological Basis Of Ip-10 As a Readout Marker In CMI mentioning
confidence: 99%
“…Furthermore, when RA FLS were stimulated with the combination of IL-27 and TNF␣ or IL-1␤, a synergistic effect was demonstrated for ICAM-1 and VCAM-1 and the release of CXCL9 and CXCL10. IL-27 can also induce TNF␣ and IL-1␤ production in primary human monocytes (9). Moreover, IL-27 stimulation results in increased IgG production of B cells, IL-17 production of CD4ϩ T cells, and collagen synthesis of fibroblasts in SSc patients compared with healthy controls; thus, IL-27 contributes to disease development in SSc patients (6).…”
Section: Interleukin-27: a Master Regulator In Inflammation Ursula Fementioning
confidence: 99%
“…IL-27 can synergize with IL-12 to promote production of interferon-␥ (IFN␥) by CD4ϩ, CD8ϩ, and NK T cells (2). Furthermore, IL-27 can induce production of several proinflammatory mediators, such as IL-1␤, TNF␣, IL-18, and IL-12, as well as chemokines and adhesion molecules and can induce the production of perforin and granzyme B in CD8ϩ T cells (9)(10)(11)(12). In primary monocytes, IL-27 is a potent inducer of IL-6, IFN␥-inducible 10-kd protein, macrophage inflammatory protein 1␣ (MIP-1␣), and MIP-1␤, an effect mediated through STAT-1, STAT-3, and NF-B activation (9).…”
Section: Interleukin-27: a Master Regulator In Inflammation Ursula Fementioning
confidence: 99%
See 1 more Smart Citation